Daily Stressors in Primary Education Students. (March 2015) - Fernández-Baena, F. Javier; Trianes, María V.; Escobar, Milagros; Blanca, María J.; Muñoz, Ángela M.
Daily stress can have a bearing on children's emotional and academic development. This study aimed to assess daily stressors and to determine their prevalence among primary education students, taking into account their gender, academic year, social adaptation, and the school location. A sample of 7, 354 Spanish schoolchildren aged between 6 and 13 years (boys, N = 3, 777, girls, N = 3, 577; M = 10.32, SD = 1.47) completed the Children's Daily Stressors Inventory (Inventario de Estrés Cotidiano Infantil, IECI in Spanish). Based on the IECI cut-offs, the majority of participants reported an absence of daily stress (68%) or only mild stress (23.2%). The prevalence of severe daily stress was 8.7%. While broadly positive, these results regarding the incidence of daily stressors in childhood highlight the need to teach children effective strategies for coping with their day-to-day problems. Intervention of this kind would be especially important for children from socially and economically disadvantaged areas and for those who present behavioral and emotional difficulties such as aggressive or inhibited behavior.